Acquired resistance in oncogene-addicted non-small-cell lung cancer. (10th July 2018) - Sini, Claudio; Tuzi, Alessandro; Rossi, Giovanni; Russo, Alessandro; Pezzuto, Aldo
The advance of tyrosine kinase inhibitors has profoundly changed the therapeutic algorithm of non-small-cell lung cancer in molecularly selected patients. However, benefit from these agents is often transient and usually most patients progress within 12 months from treatment. Novel and more potent and selective tyrosine kinase inhibitors have been developed to overcome acquired resistance; however, these agents are once again associated with only temporary benefit and patients frequently develop secondary resistance, a heterogeneous phenomenon that involves different molecular mechanisms simultaneously. The aim of our paper is to provide a comprehensive overview of the mechanisms of acquired resistance in oncogene-addicted non-small-cell lung cancer, focusing on the two most studied target, EGFR mutations and ALK translocation, and reviewing the main challenges in clinical practice.